Carrier Scattering Mechanisms: Identification via the Scaling Properties of the Boltzmann Transport Equation. Issue 1 (1st November 2020) - Majdi, Saman; Djurberg, Viktor; Suntornwipat, Nattakarn; Gabrysch, Markus; Isberg, Jan
Abstract: A method based on the scaling properties of the Boltzmann transport equation is proposed to identify the dominant scattering mechanisms that affect charge transport in a semiconductor. This method uses drift velocity data of mobile charges at different lattice temperatures and applied electric fields and takes into account the effect of carrier heating. By performing time‐of‐flight measurements on single‐crystalline diamond, hole and electron drift velocities are measured under low‐injection conditions within the temperature range 10–300 K. Evaluation of the data using the proposed method identifies acoustic phonon scattering as the dominant scattering mechanism across the measured temperature range. The exception is electrons at 100–200 K where conduction‐band valley repopulation has a prominent effect. At temperatures below ≈80 K, where valley polarization is observed for electrons, transport dominated by acoustic phonon scattering is observed in different valleys separately. The scaling model is additionally tested on data from highly resistive gallium arsenide samples to demonstrate the versatility of the method. In this case, impurity scattering can be ruled out as the dominant scattering mechanism in the samples for the temperature range 80–120 K. Abstract : A novel method is proposed to identify the dominant scattering mechanisms that affect charge transport in a semiconductor. The method uses drift velocity data of mobile charges at different lattice temperatures and applied electric fields and is based on scaling properties of the Boltzmann transport equation to take into account the effects of carrier heating.